(untitled) (Journal of Parents and Teachers, 2014)
Starting from the premise that the student should be the one who participates actively in the construction of his own knowledge and a daily resource such as soap, the author of the article proposes a set of dynamics that allow to work diverse subjects with a common nexus: soap.